Blue carbon storage of tidal flats and salt marshes: A comparative assessment in two Chinese coastal areas - Zhou, Jinge; Zhang, Lulu; Zhang, Jingfan; Gan, Shuchai; Lu, Zhe; Qin, Guoming; Huang, Xingyun; Chen, Han; He, Hua; Li, Yongxing; Li, Yingwen; Li, Hui; et al. (Palaeogeography, palaeoclimatology, palaeoecology, 2024)
Coastal wetlands are blue carbon (C) reservoirs and play an important role in mitigating climate change by efficiently capturing and storing organic carbon (OC). However, assessments of blue C sequestration focus primarily on soil organic carbon (SOC) inventories of vegetated coastal ecosystems and often neglect the potential of tidal flats to sequestrate C. To address the issue, a comparative assessment was carried out for two representative coastal wetlands in China: the Yellow River Delta and Yancheng coastal wetlands. The study focused on distinct types of coastal ecosystems including unvegetated tidal flats and three types of salt marshes vegetated by either Spartina alterniflora, Suaeda salsa, or Phragmites australis. We combined field sampling and data synthesis to assess the OC stock of different coastal areas and evaluate the regional OC storage. The results indicated that vegetated salt marshes exhibited higher OC stocks per unit area compared to unvegetated tidal flats in both regions. Interestingly, tidal flats in the Yellow River Delta displayed comparable OC stocks to S. salsa marsh on the Yancheng coast. The regional OC storage was estimated to be 5.64 ± 0.61 Tg C for the Yellow River Delta and 9.96 ± 1.52 Tg C for the Yancheng coast. Tidal flats with low SOC stock per unit area were the primary contributors to regional OC storage, accounting for over 75 % of the total. This predominance was attributed to the extensive distribution of tidal flats along China's coast, indicating their significant potential as blue C sinks. Overall, this study provides insights into the OC storage potential of various wetland types in China and highlights the importance of considering tidal flats in estimates of blue C sequestration. •The salt marsh and tidal flat's capacity to sequester blue carbon was compared.•Tidal flats are significant contributors to regional OC storage.•Vegetated salt marshes have higher OC stocks per unit area compared to unvegetated tidal flats.•The study provides an assessment of the OC storage potential of various wetland types in China.